Estudio cinético de la reacción de reducción entre azul de metileno y ácido ascórbico: variables que influyen sobre la velocidad global de reacción - Gomez, Germán Ernesto (2012)
In this work, the reduction reaction between methylene blue and ascorbic acid in aqueous solution is analyzed using an spectrophotometric method. In order to approach this experience a methodology in five days have been designed. The objective is facilitate the learning and integration of the basic laws of reaction kinetics to the Degree in Chemistry students. The reaction order is analyzed, the specific rate is determined and the influence of variables such as reactants concentration, ionic strength and reaction medium in the discoloration of the dye are studied.